2012
DOI: 10.1590/s1415-47572012005000066
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale spatial genetic structure of Dalbergia nigra (Fabaceae), a threatened and endemic tree of the Brazilian Atlantic Forest

Abstract: The Atlantic Forest is one of the most diverse ecosystems in the world and considered a hotspot of biodiversity conservation. Dalbergia nigra (Fabaceae) is a tree endemic to the Brazilian Atlantic Forest, and has become threatened due to overexploitation of its valuable timber. In the present study, we analyzed the genetic diversity and fine-scale spatial genetic structure of D. nigra in an area of primary forest of a large reserve. All adult individuals (N = 112) were sampled in a 9.3 ha plot, and genotyped f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 63 publications
1
20
0
2
Order By: Relevance
“…The majority part of genetic variation (60%) was distributed among populations and 40% was distributed within populations, according to the AMOVA results. The species with autofecudation exhibit greater genetic diversity among the populations (Buzatti et al, 2012), whereas this is different for the plants with high rates of alogamy. In a study by Santos-Garcia et al (2012) with microsatellite markers, S. capitata (which may present alogamia above 20%) did not present a correlation between the genetic distance and the collection sites, although few accesses by collection site were considered by these authors.…”
Section: Resultsmentioning
confidence: 92%
“…The majority part of genetic variation (60%) was distributed among populations and 40% was distributed within populations, according to the AMOVA results. The species with autofecudation exhibit greater genetic diversity among the populations (Buzatti et al, 2012), whereas this is different for the plants with high rates of alogamy. In a study by Santos-Garcia et al (2012) with microsatellite markers, S. capitata (which may present alogamia above 20%) did not present a correlation between the genetic distance and the collection sites, although few accesses by collection site were considered by these authors.…”
Section: Resultsmentioning
confidence: 92%
“…Most of the genetic variation (60%) was among populations and 40% within populations, according to the AMOVA results. Species with auto fecundation exhibit greater genetic diversity among populations (Buzatti et al, 2012), which does not happen for plants with high rates of allogamy. A study by Santos Garcia et al (2012) with microsatellite markers, S. capitata (which may present allogamy above 20%) did not show a correlation between the genetic distance and the collection sites, although these authors examined few samples per collection site.…”
Section: Resultsmentioning
confidence: 97%
“…These inbreeding coefficients are substantially higher than those displayed by other insect- N, number of individuals sampled; F 1 , pairwise kinship in the first distance class (up to 10 m); b, regression slope of pairwise kinship with the logarithm of distance; Sp, Sp statistic (see text). Values followed by *** were statistically different from zero (p < 0.001); standard error (SE) is indicated in parentheses pollinated forest tree species such as Dalbergia nigra (F IS = 0.08), which is mainly pollinated by bees (Buzatti et al 2012), Cabralea canjerana (F IS = 0.06) pollinated by moths (de Oliveira Melo et al 2014), or Prunus africana (F IS = 0.08-0.19), whose main pollinators are Hymenoptera and Diptera (Berens et al 2014). Previous studies have also revealed a heterozygote deficit in A. colubrina var.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of spatial patterns of genetic diversity is fundamental for the conservation of native forest tree species since it can inform the design of conservation strategies (Frankham 2003;Escudero et al 2003;Davies et al 2013). Fine-scale spatial genetic structure (FSGS), defined broadly as the non-random spatial distribution of genotypes, has been described in many plant populations (see reviews in Vekemans and Hardy 2004;Troupin et al 2006;Hardy et al 2006;Dick et al 2008;Buzatti et al 2012;Berens et al 2014;Ewédjè et al 2017). FSGS is shaped by the complex interplay of microevolutionary processes (i.e., genetic drift, gene flow, and natural selection) and mating system (Epperson 2003;Dick et al 2008).…”
Section: Introductionmentioning
confidence: 99%